Rancang Bangun Aplikasi Digital Perpustakaan Berbasis Web Di Smpk Santa Maria Kota Palangka Raya - Cristivioni, Cristivioni; Geges, Septian (Journal of Information Technology and Computer Science, 2022)
This research will discuss the use of information technology for the library at SMPK Santa Maria, Palangka Raya City. This digital library application can assist in making library transactions, because SMPK Santa Maria is still manual, that is, library transactions are carried out by writing the borrower's name and the book data borrowed in the library book. The methodology used in making this website is waterfall, with stages, namely the Requirements Definition stage using a flowchart, Requirements Analysis and Definition through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and database. Implementation and Unit Testing with programming languages namely HTML, PHP, CSS, Bootstrap, Javascript, and MySQL, Integration and System Testing using the Blackbox Method.On this website there are several features, namely the homepage, Manage member data, Manage book data, Manage fine data, Manage book location data, print member reports, print transaction reports, Manage loan transaction data, Manage return transaction data, and library floor plan information (shelf book). With the aim that librarians can easily manage data on borrowing books by members.